Promising Therapeutic Targets for Treatment of Rheumatoid Arthritis - Huang, Jie; Fu, Xuekun; Chen, Xinxin; Li, Zheng; Huang, Yuhong; Liang, Chao (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a systemic poly-articular chronic autoimmune joint disease that mainly damages the hands and feet, which affects 0.5-1.0% of the population worldwide. Nonsteroidal anti-inflammatory drugs (NSAIDs) were first used to treat RA, but owing to the significant side effects, disease-modifying antirheumatic drugs (DMARDs) were widely applied in RA clinic. Unfortunately, some patients treated by DMARDs have no response, which puts forward new requirements for special targets and researches. Studies show that understanding different pathways of RA pathogenesis and the role of different molecules in RA will help improve the current diagnostic tools for the development of disease-modifying therapies. In this review, both conventional and emerging targets in proteins, small molecular metabolites and epigenetics in relation to RA mainly are discussed, with a focus on the mechanism resulted inflammation, which help researchers design or synthesize novel medications. Although some of these agents aiming these targets have been demonstrated no good efficacy in patients, it is clear that these targets exert an irreplaceable function in the development of RA, and the understanding for underlying molecular signal pathways involved these targets may contribute to the improvement of targeted therapies for RA patients.